Wetland Link International – A Global Network for Wetland Educators - Rostron, Chris (Journal of Wetlands Ecology, 2009)
Wetland Link International (WLI) was set up in 1991, in order to strengthen wetland education networks through wetland education centres, and has a Memorandum of Co-operation with Ramsar to deliver CEPA support internationally. The definition of a ‘wetland education centre’ is broad, encompassing large built centres with interactive exhibits and thousands of visitors, to small community-run projects with little infrastructure. Anywhere that people are working to deliver messages about wetland conservation could be included. The network now has 350 members across the globe, and works with regional networks including WLI Asia and NorBalWet. DOI: 10.3126/jowe.v2i1.1856 Journal of Wetlands Ecology, (2009) Vol.2, pp.46